2016
DOI: 10.3945/ajcn.116.139030
|View full text |Cite
|
Sign up to set email alerts
|

Transcobalamin 776C→G polymorphism is associated with peripheral neuropathy in elderly individuals with high folate intake

Abstract: Background: The 776C/G polymorphism of the vitamin B-12 transport protein transcobalamin gene (TCN2) (rs1801198; Pro259Arg) is associated with a lower holotranscobalamin concentration in plasma. This effect may reduce the availability of vitamin B-12 to tissues even when vitamin B-12 intake is adequate. Clinical outcomes associated with vitamin B-12 insufficiency could potentially be worsened by high folate intake. Objective: We determined the association of the TCN2 776C/G polymorphism and folate intake with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Similarly, in elderly people with the transcobalamin 776GG genotype, which affects uptake of vitamin B 12, the risk of peripheral neuropathy was three times that of those with the CC genotype; the risk associated with the GG genotype was doubled in those whose folate was twice the recommended allowance (odds ratio 6.9 versus 3.3) 26. After fortification was introduced in the US the prevalence of low vitamin B 12 levels increased even in the absence of macrocytosis or anaemia 27…”
Section: Problems After Fortificationmentioning
confidence: 99%
“…Similarly, in elderly people with the transcobalamin 776GG genotype, which affects uptake of vitamin B 12, the risk of peripheral neuropathy was three times that of those with the CC genotype; the risk associated with the GG genotype was doubled in those whose folate was twice the recommended allowance (odds ratio 6.9 versus 3.3) 26. After fortification was introduced in the US the prevalence of low vitamin B 12 levels increased even in the absence of macrocytosis or anaemia 27…”
Section: Problems After Fortificationmentioning
confidence: 99%
“…Thus, with only 4 studies included, the meta-analysis on the association between rs1801198 and MMA lacked statistical power. The Funnel plot showed risk of bias that was related to studies that were reported by Sawaengsri et al (36) and McCaddon et al (30) in relation to the vitamin B-12 meta-analysis (Supplemental Figure 1). Table S1, Online Supporting Material Supplemental Table 1.…”
Section: Other Ocm Markersmentioning
confidence: 99%
“…When all studies were included in the meta-analysis, the homocysteine concentration was not significantly higher in subjects with the GG genotype than in those with a CC genotype with an SMD 6 SE of 0.112 6 0.058 [95% CI: 20.020, 0.240; P = 0.09 (HKSJ)] and an I 2 of 36.23% (95% CI: 0.00%, 68.66%; P = 0.11) ( Figure 2C, Table 5). The funnel plot showed risk of bias that was related to the study by Sawaengsri et al (36) (Supplemental Figure 1). When the metaanalysis included only the 8 studies in European-ancestry subjects (14,(26)(27)(28)(29)(33)(34)(35), homocysteine was significantly higher in subjects who harbored the GG genotype than in those with the CC genotype with an SMD 6 SE of 0.070 6 0.021 [95% CI: 0.020, 0.120; P = 0.01 (HKSJ)] and no heterogeneity (I 2 = 0.00%; 95% CI: 0.00%, 49.59%; P = 0.73) (Supplemental Figure 1, Figure 2C, Table 5).…”
Section: Homocysteinementioning
confidence: 99%
See 1 more Smart Citation
“…Further adding to the complexity of gene-nutrient interactions and their effects on disease susceptibility and severity are the constellations of interactive polymorphisms in one-carbon metabolism, together with substrate and cofactor availability, all of which may affect resultant phenotypes (1). The article by Sawaengsri et al (2) in this issue of the Journal, which reports that the common 776C/G polymorphism in the transcobalamin (TCN2) vitamin B-12 transporter gene is associated with peripheral neuropathy in elderly individuals with high folate intakes, informs on the currently vexed question of folate fortification and supplement use.…”
mentioning
confidence: 99%